Combined inhibition of complement and CD14 improved outcome in porcine polymicrobial sepsis. Issue 1 (December 2015) - Skjeflo, Espen; Sagatun, Caroline; Dybwik, Knut; Aam, Sturla; Urving, Sven; Nunn, Miles; Fure, Hilde; Lau, Corinna; Brekke, Ole-Lars; Huber-Lang, Markus; Espevik, Terje; Barratt-Due, Andreas; et al.
Abstract Introduction Sepsis is an exaggerated and dysfunctional immune response to infection. Activation of innate immunity recognition systems including complement and the Toll-like receptor family initiate this disproportionate inflammatory response. The aim of this study was to explore the effect of combined inhibition of the complement component C5 and the Toll-like receptor co-factor CD14 on survival, hemodynamic parameters and systemic inflammation including complement activation in a clinically relevant porcine model of polymicrobial sepsis. Methods Norwegian landrace piglets (4 ± 0.5 kg) were blindly randomized to a treatment group (n = 12) receiving the C5 inhibitor coversin (OmCI) and anti-CD14 or to a positive control group (n = 12) receiving saline. Under anesthesia, sepsis was induced by a 2 cm cecal incision and the piglets were monitored in standard intensive care for 8 hours. Three sham piglets had a laparotomy without cecal incision or treatment. Complement activation was measured as sC5b-9 using enzyme immunoassay. Cytokines were measured with multiplex technology. Results Combined C5 and CD14 inhibition significantly improved survival (p  = 0.03). Nine piglets survived in the treatment group and four in the control group. The treatment group had significantly lower pulmonary artery pressure (p  = 0.04) and ratio of pulmonary artery pressure to systemic artery pressure (p  < 0.001). Plasma sC5b-9 levels were significantly lower in the treatment group (p  < 0.001) and correlated significantly with mortality (p  = 0.006). IL-8 and IL-10 were significantly (p  < 0.05) lower in the treatment group. Conclusions Combined inhibition of C5 and CD14 significantly improved survival, hemodynamic parameters and inflammation in a blinded, randomized trial of porcine polymicrobial sepsis.